Postoperative symptom changes following uterine artery embolization for uterine fibroid based on FIGO classification - Yoshimi Nozaki; Shiori Takeuchi; Masafumi Arai; Yoshiki Kuwatsuru; Hiroshi Toei; Shingo Okada; Hitomi Kato; Naoko Saito; Takamichi Nobushima; Keisuke Murakami; Mari Kitade; Ryohei Kuwatsuru (CVIR Endovascular)
Abstract Background Classifying uterine fibroid using the International Federation of Gynecology and Obstetrics (FIGO) classification system assists treatment decision-making and planning. This study aimed to study whether different fibroid locations influence clinical outcomes following uterine artery embolization (UAE). Methods This is a retrospective cohort study of patients who underwent UAE for symptomatic uterine fibroid between December 2016 and January 2023 at our hospital. Changes in mean fibroid volume were compared based on MR images. Menstrual pain, excessive flow symptoms, and treatment satisfaction before UAE and 6 months after UAE were compared. Results A total of 149 premenopausal patients (mean age 45.7 ± 2.7 years) were included for analysis (FIGO 2/3, n = 57; FIGO 4–7, n = 92). Baseline menstrual pain, fibroid, and uterine volume before UAE were comparable between the two FIGO groups (p > 0.05). The menstrual flow index was higher for the FIGO 2/3 group (mean ± SD [min–max]: 9.4 ± 1.4 [4–10] vs 8.0 ± 2.3 [0–10], p < 0.001). Six months after UAE, the improvements in menstrual flow index (mean ± SD]: -3.7 ± 2.6 vs -2.6 ± 2.2, p = 0.035), fibroid volume (mean ± SD: -54.7 ± 21.7% vs -39.8 ± 16.2%, p < 0.001), and uterine volume (mean ± SD: -38.2 ± 16.3% vs -31.1 ± 11.6%, p = 0.008) in the FIGO 2/3 group were significantly higher than the FIGO 4–7 group. Both groups had comparable improvements in menstrual pain index (-2.1 ± 2.6 vs -1.8 ± 2.5, p = 0.008) and 88% of the patients were satisfied or very satisfied overall. Conclusion UAE treatment satisfaction was high for patients with fibroids at different FIGO stages. UAE treatment outcomes were better for patients with fibroids affecting the endometrium (FIGO 2/3). Level of evidence 3B, Retrospective observational study.